The distribution of the bft alleles among enterotoxigenic Bacteroides fragilis strains from stool specimens and extraintestinal sites - KARAHASAN, AYŞEGÜL; GÜLLÜOĞLU, MAHMUT BAHADIR; ÜLGER, NURVER (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2006)
Enterotoxigenic Bacteroides fragilis (ETBF) has been implicated in diarrhoeal illness in animals and humans. Recent data Suggest that ETBF is associated with flares of inflammatory bowel disease. Toxigenicity is attributed to expression of a toxin referred to as fragilysin, which stimulates fluid accumulation in ligated intestinal segments and alter the morphology or human intestinal cells. Three different isoforms or variants of the enterotoxin gene, designated bft-1, bft-2, and bft-3, have been identified. In this study we investigated the distribution of bft alleles among ETBF strains in stool specimens from patients with colon cancer (n:31), the control patients (n: 8) and extraintestinal sources (n: 15). We used restriction fragment length polymorphism analysis of the PCR-amplified enterotoxin gene and sequencing the PCR-product to detect the isoforms of bft gene. Among the stool strains, bft-1 was found to be more common than bft-2; as it was detected 27 of 31 strains from colon cancer patients and 7 of 8 control strains. The bft-1 isoform was also found in almost all isolates from extraintestinal sites. No bft-3 subtype was detected among all tested strains. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: enterotoxigenc; Bacteroides fragilis; colon cancer; fragilysin; bft alleles; INFLAMMATORY-BOWEL-DISEASE; METALLOPROTEASE TOXIN GENE; CHILDREN; DIARRHEA; JAPAN